2020
DOI: 10.21776/ub.ijabs.2020.28.1.5
|View full text |Cite
|
Sign up to set email alerts
|

FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND FINANCIAL MANAGEMENT BEHAVIOR: SELF–CONTROL AS MEDIATING

Abstract: Purpose — This research aims to analyze the factors influencing financial management behavior in employees of Islamic University "45" Bekasi because financial behavior is a very important issue at this time. Design/methodology/approach — The sampling technique used for this research is purposive sampling with the total population is 305 employees and samples taken were 81 employees. The data used primary data and analyzed data using smart PLS. Findings — The results of the research state that financial know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
1
12
0
5
Order By: Relevance
“…Instead, they stated that the impact is indirect. On the other hand, other research [19] found that self-control mediated a partial effect of financial knowledge and financial attitudes on financial management behavior. Financial behavior was also found to be positively influenced by financial attitude and self-control [10].…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…Instead, they stated that the impact is indirect. On the other hand, other research [19] found that self-control mediated a partial effect of financial knowledge and financial attitudes on financial management behavior. Financial behavior was also found to be positively influenced by financial attitude and self-control [10].…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 88%
“…To summarize, self-control has been found to have a positive impact on financial behavior. This means that people with more self-control are better at managing their finances, not engaging in compulsive buying, and not getting into debt [2,3,4,6,10,12,18,19,20,21,28]. Besides self-control, some other psychological factors have been found to influence financial behavior.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Moreover, Norvilitis et al [5] measured perceived financial wellbeing with the personal sensation of financial confidence and security, and the results show that this definition seems to be associated with psychological wellbeing. Previous literature on financial satisfaction has shed light on the impact of financial literacy with a moderating variable of financial behavior [6,7], financial management behavior and attitude [8], financial capability [9,10], and credit use [11]. Unlike previous studies, this study further investigates the branch of financial capability in MIE specifically.…”
Section: Original Research Articlementioning
confidence: 98%
“…Attitude towards one's money is how one has views and behaviors about money, the main primary need of humans is money, money can make humans think irrationally (Siswanti & Halida, 2020). Social pressure is the condition of individuals when they have money, how do individuals deal with it, when they have a lot of money, individuals are confused about what the money is and whether they can refrain from the money they have, this affects financial management behavior, the higher a person can refrain from the money they have.…”
Section: Financial Attitudementioning
confidence: 99%
“…It is not enough that having knowledge only, but must be followed by financial attitudes, namely one's assessment of finances, more towards ways of thinking, opinions, and assessments of individual finances that are applied through attitudes so that they can manage its finances (Kusani et al, 2019, Dwiastanti, 2017. Financial attitudes can shape the style or way people shopping, spending money, deposit, and save money (Siswanti & Halida, 2020).…”
Section: Introductionmentioning
confidence: 99%